ANALISIS VISUAL ILUSTRASI ANIMASI PADA IKLAN TVC DJARUM BEASISWA BULUTANGKIS 2018 - Christina Natalia Hartono (Universitas Katolik Soegijapranata, Semarang, 2021)
TVC Djarum badminton scholarship 2018 advertisement is the only TVC PB Djarum that applies 2D animation, since TVC Djarum badminton scholarship has existed since 2007. This TVC’s 2018 was able to get the highest number of viewers on the official account of PB Djarum's Youtube platform. Thus, it was found the effect of animation on this TVC. Visually, the 2D animation in this TVC depicts children's characters and figures. This study aims to analyze how 2D animation in the form of illustrations of children playing badminton is applied to this TVC advertisement. Analysis of the application of this animation can examine the visualization of meaning, uniqueness, colors used, and the role of the illustration itself. The purpose of this study was to determine the character and meaning of the animation applied to the 2018 TVC Djarum Badminton Scholarship ad. literature review. This study found that TVC videos targeting the children's category would be better off using a 2D animation approach, using a cartoon style, and displaying color visuals that are impressively cheerful, enthusiastic, active, and courageous.